2015
DOI: 10.1002/pmic.201500017
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of phosphoproteome dynamics in embryonic development of zebrafish (Danio rerio)

Abstract: The zebrafish (Danio rerio) is a popular animal model used for studies on vertebrate development and organogenesis. Recent research has shown a similarity of approximately 70% between the human and zebrafish genomes and about 84% of human disease-causing genes have common ancestry with that of the zebrafish genes. Zebrafish embryos have a number of desirable features, including transparency, a large size, and rapid embryogenesis. Protein phosphorylation is a well-known PTM, which can carry out various biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 85 publications
0
26
0
Order By: Relevance
“…A total of 97.7% of Kcr proteins and 76.8% of Kcr sites in zebrafish significantly overlapped with humans. Our previous study showed that 69% of zebrafish phosphoproteins were conserved in humans 9 . In addition, 51.7% of zebrafish Kac sites overlapped with humans and 34.5% of Kac sites were identified as human Kac sites 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 97.7% of Kcr proteins and 76.8% of Kcr sites in zebrafish significantly overlapped with humans. Our previous study showed that 69% of zebrafish phosphoproteins were conserved in humans 9 . In addition, 51.7% of zebrafish Kac sites overlapped with humans and 34.5% of Kac sites were identified as human Kac sites 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Among known PTMs, the phosphoproteome in zebrafish embryos has been well-studied; 1067 endogenous phosphorylation sites from 60 embryos were identified in 2008 8 . Moreover, we previously identified 3500 non-redundant phosphorylation sites on 2166 phosphoproteins and quantified 1564 phosphoproteins in developing zebrafish embryos 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The transparency of zebrafish embryos allows rapid optical assessment of phenotypic changes associated with target modulation. Interestingly, sequencing showed that over 70% of human genes have a functional zebrafish homolog, including at least 84% of proteins implicated in human disease . For comparison, protein‐coding regions of human and mouse genomes are 85% similar .…”
Section: Overview Of the Models Used In The Current Process Of Drug Dmentioning
confidence: 99%
“…Development of high‐throughput techniques enabled obtaining the complex expression profiles in living systems. The annotated genome sequence for zebrafish is currently available and many proteomic studies on zebrafish were performed to analyze embryogenic stages , organ systems , or pathological effects of genetic mutations and toxins . A proteome profiling of adult zebrafish organs previously performed by Abramsson et al.…”
mentioning
confidence: 99%
“…The annotated genome sequence for zebrafish is currently available [7] and many proteomic studies on zebrafish were performed to analyze embryogenic stages [8,9], organ systems [10,11], or pathological effects of genetic mutations [12] and toxins [13][14][15]. A proteome profiling of adult zebrafish organs previously performed by Abramsson et al [10] showed high percentage (40%) of brain-specific proteins.…”
mentioning
confidence: 99%